In Search of Stars: Network Formation among Heterogeneous Agents - Alja Ule; Jacob K. Goeree; Arno Riedl (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper reports results from a laboratory experiment on network formation among heterogeneous agents. The experimental design extends the Bala-Goyal (2000) model of network formation with decay and two-way flow of benefits by allowing for agents with lower linking costs or higher benefits to others. Furthermore, agents types may be common knowledge or private information. In all treatments, the (efficient) equilibrium network has a star structure. With homogeneous agents, equilibrium predictions fail completely. In contrast, with heterogeneous agents stars frequently occur, often with the high-value or low-cost agent in the center. Stars are not born but rather develop: with a high-value agent, the networks centrality, stability, and efficiency all increase over time. Probit estimations based on best-response behaviour and other-regarding preferences are used to analyze individual linking behavior. Our results suggest that heterogeneity is a major determinant for the predominance of star-like structures in real-life social networks.
Keywords: C72; C92; D82; D85; 330; Network Formation; Experiment; Heterogeneity; Private Information; Netzwerk; Soziales Netzwerk; Test; Asymmetrische Information; Theorie